Biodiversity in the coastal ecosystems of small islands and its conservation status. Issue 1 (May 2021) - Suyadi; Nugroho, D A; Irawan, A; Pelasula, D; Ruli, F; Islami, M M; Alik, R; Tala, D J.; Pay, L; Matuankotta, C; Leatemia, A S; Naroli, I
Abstract: Around 77% of Indonesian islands is small islands and Indonesia known as mega biodiversity center, but coastal biodiversity of small islands was not well documented. The objective of this study is to assess coastal biodiversity in small islands and its conservation status. The study indicated that small islands provide complex biodiversity ranging from ecosystem to species. Diversity index of mangrove: 1.4-1.8, seagrass: 1.5–1.9, coral: 1.7–2.3. Ecosystem condition in urban small island was poor and in rural small island was healthy. The islands also provide fauna diversity i.e mollusc (110 species), crabs (52 species), and coral fish (261 species). Diversity of mollusc and crabs in rural island was higher than in urban island, χ2 (1) = 1.3, p< 0.001 and χ2 (1) = 4.3, p< 0.002, respectively. Diversity index of coral fish range from 2.14 to 4.27 (mean: 3.4). Most of the biodiversity located outside protected area and main threats were ecosystem degradation, pollution, overexploitation, and sedimentation. In conclusion, small islands are important coastal biodiversity spots, but it faces tremendous threats. The study recommends better management of coastal biodiversity i.e. establishing coastal protected areas in small islands, building marine corridor, and public awareness to ensure biodiversity conservation.